Photon pair-state preparation with tailored spectral properties by spontaneous four-wave mixing in photonic-crystal fiber. - Garay-Palmett, K; McGuinness, H; Cohen, O; Lundeen, J; Rangel-Rojo, R; U'ren, AB; Raymer, MG; McKinstrie, C; Radic, S; Walmsley, I (2007)
We study theoretically the generation of photon pairs by spontaneous four-wave mixing (SFWM) in photonic crystal optical fiber. We show that it is possible to engineer two-photon states with specific spectral correlation ("entanglement") properties suitable for quantum information processing applications. We focus on the case exhibiting no spectral correlations in the two-photon component of the state, which we call factorability, and which allows heralding of single-photon pure-state wave packets without the need for spectral post filtering. We show that spontaneous four wave mixing exhibits a remarkable flexibility, permitting a wider class of two-photon states, including ultra-broadband, highly-anticorrelated states.